Superior humidity sensor and photodetector of mesoporous ZnO nanosheets at room temperature - Gupta, Shobhnath P.; Pawbake, Amit S.; Sathe, Bhaskar R.; Late, Dattatray J.; Walke, Pravin S. (Sensors and Actuators B-Chemical, 2019)
Miniaturized sensor technology is vastly demanding multifunctional materials to fulfill many requirements simultaneously; instead of integrating various sensors into a single device. Efficient operation of these miniaturized sensors at room temperature is highly feasible and cost-effective. The humidity sensing and photodetection is precise merit of sensing in special usage like artificial skin. Sensitivity enhancement in both humidity and photodetection required the high surface area for adsorption as well as a high charge transfer mechanism. The two dimensional (2D) zinc oxide nanosheets (ZnO NS) is the ultimate structure for dimensionally confined transport properties owing to the specific surface atomic configuration that results in high sensitivity, low operating temperature, fast response and recovery, and improved selectivity. Furthermore, introducing porosity into 2D nanostructures has opened new opportunities to enhance the efficiency of sensors and detectors via increasing large surface area and tunable physical and chemical properties. Here we report preparation of mesoporous and highly crystalline 2D ZnO NS by a single step, template free, cost-effective chemical method. The structural and morphological characterizations of ZnO NS are carried out using XRD, FESEM, XPS, TEM respectively. The high-resolution TEM images emphasize sheet-like morphology with a thickness of around 18-22 nm. Further the mesoporous ZnO NS (MZNS) with the pore size between 5-10 nm are achieved by simple heat-treatment. XPS and PL study is confirming the oxygen deficiency in MZNS. The MZNS exhibits an excellent responsivity than PZNS with a fast response and rapid recovery time of 25 s and 5 s respectively along with good cyclic stability which is highly crucial for smart humidity sensor. Furthermore, it considerably enhances photo-sensor performance than pristine ZnO NS (PZNS) with (similar to)1 s response time as well as (similar to)1 s recovery time along with better stability. These promising results illustrate the great potential of MZNS for next-generation humidity sensors and photodetectors.
Keywords: humidity sensor; Mesoporous; nanosheets; Photo-detector